Structure and Morphology of ZnO Nanoparticles Prepared by Sonochemical Method - Maddu, Akhiruddin; Zetria Zikri; Irzaman, Irzaman (Universitas Mandiri, 2023)
Ultrasonic wave has been utilized to synthesize the ZnO nanoparticle. ZnO is formed from a mixture of zinc acetate (ZnAc) and Natrium Hydroxide (NaOH) with various concentrations of ZnAc 0.5 M (ZnO 1:1) and 1.5 M (ZnO 3:1) and the concentration of NaOH remained at a concentration of 0.5 M. The Structure and crystal size were characterized using X-ray Diffraction (XRD), while its morphology was examined by Scanning Electron Microscopy (SEM). The results show that ZnO 1:1 has a higher (stronger) diffraction intensity than the ZnO 3:1. The crystallite size of ZnO 1:1 averaged 30.57 ± 4.31 nm while the ZnO 3:1 had an average crystallite size of 20.25 ± 7.12 nm. From the size of the crystallites ZnO particles that are formed include nanoparticles. ZnO 1:1 SEM image shows the shape of microrods in the 1:1 ZnO sample while in the 3:1 ZnO sample no microrods are formed. Based on the morphology, the 1:1 ZnO sample has an average size of 230 nm and is larger than the 3:1 ZnO sample which has an average size of 50 nm.